Numerical investigation on trimming of a single sail in a regatta - Ma, Y.; Tang, Y.; West, N.; Zhang, Z.; Lin, S.; Zheng, Q. (Sports Engineering, 2016)
In sailing regattas, the actions of sailboats are to meet, overlap, pursue, pass, anti-collide, and defend. The aerodynamic performance of a sail based on a numerical simulation method is reported in this study. The parameters affecting the sail`s aerodynamic force coefficients, namely sailing angle, attack angle, mast shape, pitch angle, and camber ratio, are analyzed. From the results, basic principles and corresponding tactics of sail trimming are discussed and recommended for the start, during the windward, running, and leeward legs, before the finish, and near the marks. Sailors in the regatta should decrease the interaction of air flows around the sail to increase the lift force. The sailing angle, attack angle, pitch angle, and camber ratio should be adjusted to the appropriate degree to speed the boat when it is balanced. Sail trimming tactics have been practiced by professional sailors in regattas during which they can be scientifically supervised to compete against each other at Olympic Games.